Surgical Repair Using Suture Bridge Technique for Triceps Tendon Avulsion - Ryogo Furuhata; Yusaku Kamata; Aki Kono; Taichi Nishimura; Shinya Otani; Hideo Morioka (Case Reports in Orthopedics)
Triceps tendon avulsion is a rarely occurring tendinous injury. Various surgical procedures, such as repair using sutures through the transosseous tunnel or suture anchors, have been reported for treating triceps tendon avulsion. However, standard surgical treatment has not yet been established. Here, we present a case of triceps tendon avulsion treated using the suture bridge technique. A 58-year-old man who fell on his left elbow from standing height presented to our hospital. Plain radiography revealed an avulsion fracture of the left olecranon process, suggesting triceps tendon avulsion. We performed surgical repair of the avulsed bone fragments and ruptured triceps tendon. We inserted suture anchors into the ulna, proximal to the fracture site, and passed the sutures through the full thickness of the triceps. Subsequently, fracture fragments were reduced and fixed by pulling them together with the triceps. We inserted knotless anchors into the ulna distal to the fracture site and fixed the avulsed bone fragments and triceps tendon using the suture bridge technique. The patient recovered well in five months and reported no elbow pain or limited range of motion. This suture bridge technique is advantageous as it prevents iatrogenic fracture and knot irritation, and it would be indicated in cases with poor bone quality or thin skin soft tissue of the olecranon.